The Atmospheres of Saturn and Titan in the Near-Infrared First Results of Cassini/vims - Baines, Kevin H.; Drossart, Pierre; Momary, Thomas W.; Formisano, Vittorio; Griffith, Caitlin A.; Bellucci, Giancarlo; Bibring, Jean-Pierre; Brown, Robert H.; Buratti, B. J.; Capaccioni, Fabrizio; Cerroni, Priscilla; Clark, Roger N.; et al. (Earth, Moon, and Planets, 2005)
International audience The wide spectral coverage and extensive spatial, temporal, and phase-angle mapping capabilities of the Visual Infrared Mapping Spectrometer (VIMS) onboard the Cassini-Huygens Orbiter are producing fundamental new insights into the nature of the atmospheres of Saturn and Titan. For both bodies, VIMS maps over time and solar phase angles provide information for a multitude of atmospheric constituents and aerosol layers, providing new insights into atmospheric structure and dynamical and chemical processes. For Saturn, salient early results include evidence for phosphine depletion in relatively dark and less cloudy belts at temperate and mid-latitudes compared to the relatively bright and cloudier Equatorial Region, consistent with traditional theories of belts being regions of relative downwelling. Additional Saturn results include (1) the mapping of enhanced trace gas absorptions at the south pole, and (2) the first high phase-angle, high-spatial-resolution imagery of CH 4 fluorescence. An additional fundamental new result is the first nighttime near-infrared mapping of Saturn, clearly showing discrete meteorological features relatively deep in the atmosphere beneath the planet's sunlit haze and cloud layers, thus revealing a new dynamical regime at depth where vertical dynamics is relatively more important than zonal dynamics in determining cloud morphology. Zonal wind measurements at deeper levels than previously available are achieved by tracking these features over multiple days, thereby providing measurements of zonal wind shears within Saturn's troposphere when compared to cloudtop movements measured in reflected sunlight. For Titan, initial results include (1) the first detection and mapping of thermal emission spectra of CO, CO 2 , and CH 3 D on Titan's nightside limb, (2) the mapping of CH 4 fluorescence over the dayside bright limb, extending to ˜ ˜750 km altitude, (3) wind measurements of ˜ ˜0.5 ms -1 , favoring prograde, from the movement of a persistent (multiple months) ...